Association between mental imagery and change of direction performance in young elite soccer players of different maturity status - Sariati, D.; Zouhal, H.; Hammami, R.; Clark, C. C. T.; Nebigh, A.; Chtara, M.; Hackney, A. C.; Souissi, N.; Granacher, U.; Ounis, O. B. (Frontiers in Psychology, 2021)
Previous studies have not considered the potential influence of maturity status on the relationship between mental imagery and change of direction (CoD) speed in youth soccer. Accordingly, this cross-sectional study examined the association between mental imagery and CoD performance in young elite soccer players of different maturity status. Forty young male soccer players, aged 10-17 years, were assigned into two groups according to their predicted age at peak height velocity (PHV) (Pre-PHV; n = 20 and Post-PHV; n = 20). Participants were evaluated on soccer-specific tests of CoD with (CoDBall-15m) and without (CoD-15m) the ball. Participants completed the movement imagery questionnaire (MIQ) with the three- dimensional structure, internal visual imagery (IVI), external visual imagery (EVI), as well as kinesthetic imagery (KI). The Post-PHV players achieved significantly better results than Pre-PHV in EVI (ES = 1.58, large; p < 0.001), CoD-15m (ES = 2.09, very large; p < 0.001) and CoDBall-15m (ES = 1.60, large; p < 0.001). Correlations were significantly different between maturity groups, where, for the pre-PHV group, a negative very large correlation was observed between CoDBall-15m and KI (r = -0.73, p = 0.001). For the post-PHV group, large negative correlations were observed between CoD-15m and IVI (r = -0.55, p = 0.011), EVI (r = -062, p = 0.003), and KI (r = -0.52, p = 0.020). A large negative correlation of CoDBall-15m with EVI (r = -0.55, p = 0.012) and very large correlation with KI (r = -0.79, p = 0.001) were also observed. This study provides evidence of the theoretical and practical use for the CoD tasks stimulus with imagery. We recommend that sport psychology specialists, coaches, and athletes integrated imagery for CoD tasks in pre-pubertal soccer players to further improve CoD related performance.